Comparison of the efficacy and safety of ultrasound-guided surgery with traditional surgery for plasma cell mastitis: a systematic review and meta-analysis - Zhang, Ti; Yao, Chang; Shi, Jianzhong; Ma, Shikun; Hu, Yue (Frontiers in Medicine, 2025)
ObjectivesThis study aims to offer an updated, comprehensive comparison of the efficacy and safety between ultrasound-guided surgery (UGS) and traditional surgery (TS) for plasma cell mastitis (PCM).MethodsStudies comparing UGS with conventional surgery for PCM were retrieved from Embase, PubMed, Web of Science, China National Knowledge Infrastructure (CNKI), and Wanfang databases (up to March 2025). Sensitivity and subgroup analyses were conducted to assess result stability and identify sources of heterogeneity. All findings were evaluated using Grading of Recommendations Assessment, Development and Evaluation (GRADE). Analyses were performed with Review Manager 5.4 and STATA 15.0.ResultsNine eligible studies, including 951 patients (486 UGS, 465 TS), were analyzed. Baseline characteristics were comparable between the groups. Pooled analysis indicated that UGS resulted in shorter operative time, lower postoperative complication rates, reduced intraoperative hemorrhage, lower visual analog scale (VAS) scores, improved efficacy, and higher satisfaction with overall appearance. Recurrence rates and pain satisfaction were comparable between the two groups. According to GRADE classification, results for efficacy, satisfaction, and mammary deformity were rated as low-quality evidence, while other outcomes were rated as very low-quality due to significant heterogeneity, imprecision, or publication bias.ConclusionEvidence suggests that UGS improves efficacy, satisfaction, and reduces postoperative complications for PCM. However, given the limited quality and quantity of the included studies, further high-quality research is needed to confirm these findings.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/.